MENGUNGKAP BENTUK BULLYING DI SEKOLAH SMPN 1 GENDING KABUPATEN PROBOLINGGO DALAM KONTEKS PEMBELAJARAN IPS PADA KELAS 7 DI ERA GENERASI Z - nur, siti; Mahfudz Sulaiman; Titik Isbandiyah (Universitas Islam Zainul Hasan Genggong, 2025)
Bullying is a repeated aggressive behavior carried out by one or more individuals to hurt, intimidate, or dominate others who are considered weaker or different. Bullying in the Generation Z era has drastically changed with the development of digital technology and social media. In addition to physical and verbal forms, bullying now more frequently occurs in the virtual world, known as cyberbullying. Generation Z, growing up alongside technological advancements, is more vulnerable to this form of aggressive behavior, as much of their social interaction takes place on digital platforms. Similarly, bullying remains a serious issue in various school environments, particularly at SMPN 1 Gending, Probolinggo Regency, where bullying behavior between students still frequently occurs. Although the school has made significant efforts by tightening regulations and increasing discipline among students, bullying, both physical and verbal, remains widespread among students. The school's efforts to create a safe and supportive environment through the enforcement of strict rules and prevention programs do not seem to have fully succeeded in reducing the frequency of bullying incidents. This situation indicates that more comprehensive and continuous interventions are needed, including educational approaches, increased parental involvement, and the development of students' social and empathetic skills, to effectively address bullying behavior at the school. This research aims to analyze the forms of bullying at SMPN 1 Gending, Probolinggo Regency, in the context of Social Studies (IPS) learning in 7th grade during the Generation Z era. This research employs a qualitative approach with a phenomenological research design. Data collection techniques in this study include interviews, observations, and documentation. Data validity is ensured through source triangulation and method triangulation. The data analysis techniques involve data collection, data reduction, data verification, and data conclusion. The informants in this study consist of 7th-grade Social Studies teachers and Counseling teachers at SMPN 1 Gending. The results of this study are as follows: 1) The forms of bullying that occur at SMPN 1 Gending include physical bullying (involving acts of physical violence such as hitting, pushing, etc.), verbal bullying (involving insults, mockery, or negative comments), social bullying (including social exclusion), and cyberbullying (a form of bullying through digital media). 2) The strategies implemented to address the issue of bullying at SMPN 1 Gending include socialization, incorporating bullying topics into classroom lessons, summoning problematic students by counseling teachers, and calling parents of students involved in bullying.